Biomechanical differences at the hemiparetic knee in people with stroke: a systematic review and meta-analysis protocol. (2nd January 2021) - Waller, Clifford; Sangelaji, Bahram; Lamb, Peter; Kuys, Suzanne; Woodley, Stephanie J.
Abstract: Background: Understanding the effect of stroke on knee biomechanics in gait is important for clinicians and practitioners who work with people with stroke. Biomechanical differences have been established between the hemiparetic knee, and the unaffected knee and healthy controls during gait. These data have not yet been systematically summarised and analysed. This protocol describes the background and methods for a systematic review and meta-analysis of three-dimensional biomechanics of the hemiparetic knee whilst walking overground, based on data collected using optical motion capture systems. Methods/Design: The review will be directed by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Two authors will independently carry out searches using Web of Science, MEDLINE, Embase, CINAHL and Scopus. The reference list of included studies will be screened for further studies by one reviewer. Observational studies and baseline data from randomised control trials will be included. Two reviewers will screen the studies, extract data and assess for bias using a modified Downs and Black quality index. Meta-analyses will be performed if sufficient data are available, and the level of evidence assessed using confidence intervals and effects sizes, and displayed in forest plots. Discussion: Findings of the review will provide further insight into the biomechanical differences at the hemiparetic knee, which may assist with outcome measurements and planning of post-stroke rehabilitation. The findings may also be used to inform future research into the biomechanical assessment of gait in people with stroke. Trial registration: Prospero registration number CRD42019137058.